Cooperative Intermediate Housing Tenures in Poland and Germany - Królikowska, Katarzyna (PRAWO i WIĘŹ, 2024)
This paper presents a comparative analysis of cooperative tenures available in housing cooperatives in Poland and Germany. The research is based on the typology that understands property rights from the moderate constructivist approach and applies them to housing tenures by means of the analysis of the distribution of specific bundles of property rights which appears to be different across the housing tenures. Innovative intermediate tenures as housing options beyond tenancy and homeownership are approached and supported for a particular reason – as remedies to address the growing European housing crisis. So, the article contains a comparative analysis of the features of cooperative housing tenures as intermediate tenures for international comparisons of „affordable” and „social housing” options.